2014
DOI: 10.2500/ajra.2014.28.4016
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Absorbable Gelatin Dressing Impregnated with Triamcinolone within the Olfactory Cleft on Polypoid Rhinosinusitis Smell Disorders

Abstract: We suggest that application of triamcinolone at the olfactory cleft can boost the effect of surgery in restoring olfactory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 28 publications
0
49
0
Order By: Relevance
“…[22][23][24] The smell threshold is determined when the bottle with the lowest butanol concentration is detected correctly 5 consecutive times. 14,[22][23][24] Smell identification tests use common odorants in order to test how well a person can detect normal environmental odors. 22 There are several smell identification tests, including the most widespread and commercially available University of Pennsylvania Smell Identification Test (UPSIT; Sensonics, Inc, Haddon Heights, NJ).…”
Section: Olfactory Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] The smell threshold is determined when the bottle with the lowest butanol concentration is detected correctly 5 consecutive times. 14,[22][23][24] Smell identification tests use common odorants in order to test how well a person can detect normal environmental odors. 22 There are several smell identification tests, including the most widespread and commercially available University of Pennsylvania Smell Identification Test (UPSIT; Sensonics, Inc, Haddon Heights, NJ).…”
Section: Olfactory Testingmentioning
confidence: 99%
“…10,11 Without clear and consistent evidence that ESS improves smell, patients' postoperative expectations need to be addressed, which includes counseling that olfactory loss may persist or even worsen despite surgery and medical therapy. 4,[12][13][14] Addressing olfaction is also important before endoscopic endonasal skull base surgery, because smell loss may occur during tumor resection or harvest of a large nasoseptal flap for reconstruction. [15][16][17][18] In a survey of practicing otolaryngologists, roughly 40% routinely discuss the potential for postoperative anosmia with patients.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of ESS on improving olfactory dysfunction has remained controversial due to lack of comprehensive evidence. Range of improvement has been reported from 25% to100% according to some prior studies; while others have reported no improvement or even reduced olfactory function following ESS [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, 14 percent of adult Americans and 10.9 % of Europeans had chronic rhinosinusitis [2]. Generally, the incidence of rhinosinusitis is 2 to 4 percent [3].…”
Section: Introductionmentioning
confidence: 99%
“…So, medical treatment is recommended after the operation. Nasal and systemic steroids are effective in the decrease of the recurrence following surgery [2]. Due to complications of the corticosteroids, alternative treatments are studied, including leukotriene antagonists such as zafirlukast, montelukast, and zileuton.…”
Section: Introductionmentioning
confidence: 99%